The polynomials [tex](x^{2} +x-1)[/tex] and [tex](x^{4} -3x^{2} +4x-3)[/tex] has a quotient of[tex](x^{2} +x-3)[/tex]. The polynomial is [tex](x^{2} +x-1)[/tex].
What is Euclid's division lemma?
Euclid's division lemma states that for any positive integers, let's say a and b the condition [tex]\rm a=bq+r[/tex], where [tex]\rm 0\leq r\leq b[/tex].
Mathematically, we can say that
Dividend = divisor × quotient + remainder
P(x) = g(x) × q(x) + r(x)
To find the divisor g(x)
[tex]x^{4} -3x^{2} +4x-3= \rm g(x)\times (x^{2} +x-3) + r(x)\\[/tex]
On dividing P(x) by q(x) we get,
[tex]x^{4} -3x^{2} +4x-3 \div (x^{2} +x-3) = \rm g(x)+0[/tex][tex](x^{2} +x-3) \times (x^{2} +x-1)\div (x^{2} +x-3) = \rm g(x)\\(x^{2} +x-1) = \rm g(x)\\[/tex]
Hence, the polynomials [tex](x^{2} +x-1)[/tex] and [tex](x^{4} -3x^{2} +4x-3)[/tex] has a quotient of [tex](x^{2} +x-3)[/tex]. The polynomial is [tex](x^{2} +x-1)[/tex].
learn more about 'Division of polynomial' here:
https://brainly.com/question/12978781